Consequence of Cattaneo-Christov heat and mass flux models on bioconvective flow of dusty hybrid nanofluid over a Riga plate in the presence of gyrotactic microorganisms and Stephan blowing impacts - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Salleh, Zabidin; Aly, Ayman A.; Rezapour, Shahram; İnç, Mustafa (Elsevier, 2024)
This study investigates the impact of the Stephan blowing and Cattaneo-Christov flux model on bioconvective flow of dusty hybrid nanofluid over a Riga plate in the presence of gyrotactic microorganisms and variable dust particles volume friction. Mass and heat phenomena are explored in the context of Stefan blowing impacts. The hybrid nanofluid consists of nanoparticles of MgO and Ag base fluid water. The Cattaneo-Christov mass and heat flux model has a significant impact on the bioconvective flow. The model predicts a slower temperature distribution and a higher concentration gradient than the traditional Fick's law and Fourier's law, respectively. The occurrence of gyrotactic microorganisms enhance the flow characteristics. This model is important for optimizing mass and heat transfer in a variety of engineering systems, including heating and cooling technologies, where effective thermal control is essential. It can be used by employing the regulated migration of microbes. By maximizing the removal of impurities, it helps with the design of sophisticated water purification systems in environmental engineering. The amalgamation of gyrotactic microorganisms and Stefan blowing effects augments the comprehension of intricate fluid dynamics, maybe resulting in advancements in microfluidic apparatuses and bioinspired technologies. In order to transform the controlling PDEs into nonlinear ODEs, a new set of non-dimensional variables is used. The MATLAB (RKF-45th) technique is then used to resolve the ODEs numerically. As the Stephan blowing parameter (0.1 <= Sb <= 1.9) ) increases, the outcomes show that the flow distributions upsurge for both the dust and fluid phases, but the dust and fluid phase thermal distributions drop.
Keywords: Dusty hybrid nanofluid; Stephon blowing; Cattaneo-Christov heat and mass flux model; Gyrotactic microorganisms; Riga plate